Effect of change of natural efficiency indicators for profitability of broiler chicken fattening - Kiss, István (Acta Agraria Debreceniensis, 2012)
I consider it important that the fattening of broiler producers in an economic sense to remain alive in the present difficult situation. This does not mean to me, that just does not generate a loss, but they do remain in their activities after income. Because if you do not have sufficient income in a given sector then the technology becomes obsolete over time and income deficit due to the possible improvements are still lagging behind, resulting in competitive disadvantages occur. The natural efficiency remains a priority, because fundamentally determine our competitiveness in the broiler production. In the present study, scenario analysis can prove the veracity of my claim, in point of the three most important natural efficiency indicators. The natural efficiency indicators of a company compared to the natural effectiveness of our country and the our competitions (Western-European countries).